ANALISIS FASIES AIRTANAH DAERAH PARAKAN OMAS DAN SEKITARNYA, KECAMATAN RUMPIN, KABUPATEN BOGOR, JAWA BARAT, DALAM MENENTUKAN FASIES AIRTANAH: ANALYSIS OF GROUNDWATER FACIES IN PARAKAN OMAS AND SURROUNDING REGIONS, RUMPIN DISTRICT, BOGOR REGENCY, WEST JAVA, IN TO THE DETERMINE GROUNDWATER FACIES. - Ruli Firmanda; Suherman Dwi Nuryana; Muhammad Adimas Amri (Journal of Geoscience Engineering & Energy (JOGEE), 2022)
The research area is located in Parakan Omas Village, Rumpin District, Bogor Regency, West Java Province. The background of this research was to determine the chemical properties of groundwater in the springs in the Parakan Omas area. The method used is taking samples of springs from springs and chemical analysis of the main ions (Mg⁺, Ca²⁺, Na⁺, K⁺, Cl⁻, SO₄²⁻, HCO₃⁻, CO₃⁻) and getting 5 samples of springs entered into the laboratory. The purpose of this study was to determine the chemical characteristics of groundwater in Rumpin sub-district. Lithological conditions affect groundwater facies, volcanic rocks cause groundwater to contain mineral cations Mg⁺ and Ca²⁺ with varying anions while alluvium layers in land areas will cause groundwater to be rich in sodium (Na⁺) minerals with anions in the form of chloride (Cl⁻) or sulfate ( SO₄²⁻). Data analysis using piper trilinear diagram. The diagram shows that there are 2 types of facies in the dominant research area, namely Sodium Potassium Bicarbonate (Na+ + K+ HCO3- ) and Calcium Magnesium Bicarbonate (Ca2+ + Mg2+HCO3⁻).